Indonesian Undergraduate Students’ Perceptions of Project-Based Learning in Critical Reading Class - Arien Kartika (Universitas Negeri Makassar, 2020)
Along with the increasing popularity of Project-Based Learning (PBL), teachers are aware of the benefits of PBL to implement it in their classroom. The literature has shown that the use of PBL can enhance students' skills, ability, and interest while learning because it focuses on students learning process than the teaching process. However, in a context in Indonesia, there is still a lack of research perceptions of PBL especially in the Critical reading class and collected data to determine if PBL has positive impacts on students learning in the university. The research is aimed at investigating students' perceptions about PBL by implementing a half-semester project in the Critical Reading class. This study employed a mixed-method that includes both quantitative and qualitative data collection and analysis by involving undergraduate students of the 4th semester who take a critical reading class in Universitas Sebelas Maret. It is expected to show us an example of PBL practice in critical reading class and how students thought about its implementation and improvement. This study provides a students' perceptions of PBL in critical reading class. The results add to the findings and discussion on what makes the method of teaching PBL more successful and have practical implications for classroom teaching.